“Wellbeing Through Reading”: The Impact of a Public Library and Healthcare Library Partnership Initiative in England - Phul, Anita; Gorring, Hélène; Stokes, David (Evidence Based Library and Information Practice, 2024)
Objective – This project sought to build upon a reader development tool, Many Roads to Wellbeing, developed by a health librarian in a mental health NHS Trust in Birmingham, England, by piloting reading group sessions in the main public library in the city using wellbeing-themed stories and poems. The aim was to establish whether a “wellbeing through reading” program can help reading group participants to experience key facets of wellbeing as defined by the Five Ways to Wellbeing.Methods – The program developers ran 15 monthly sessions at the Library of Birmingham. These were advertised using the Meetup social media tool to reach a wider client base than existing library users; members of the public who had self-prescribed to the group and were actively seeking wellbeing. A health librarian selected wellbeing-themed short stories and poems and facilitated read aloud sessions. The Library of Birmingham provided facilities and a member of staff to help support each session.Results – A total of 131 participants attended the 15 sessions that were hosted. There was a 95% response rate to the questionnaire survey. Of the respondents, 91% felt that sessions had helped them to engage with all of the Five Ways to Wellbeing. The three elements of Five Ways to Wellbeing that participants particularly engaged with were Connect (n=125), Take Notice (n=123), and Keep Learning (n=124).Conclusion – The reading program proved to be successful in helping participants to experience multiple dimensions of wellbeing. This project presents a new way of evaluating a bibliotherapy scheme for impact on wellbeing, as well as being an example of effective partnership working between the healthcare sector and a public library.